PKM2 regulates the Warburg effect and promotes HMGB1 release in sepsis - Yang, Liangchun; Xie, Min; Yang, Minghua; Yu, Yan; Zhu, Shan; Hou, Wen; Kang, Rui; Lotze, Michael T.; Billiar, Timothy R.; Wang, Haichao; Cao, Lizhi; Tang, Daolin (Nature communications, 2014)
Increasing evidence suggests the important role of metabolic reprogramming in the regulation of the innate inflammatory response, but the underlying mechanism remains unclear. Here we provide evidence to support a novel role for the pyruvate kinase M2 (PKM2)-mediated Warburg effect, namely aerobic glycolysis, in the regulation of high-mobility group box 1 (HMGB1) release. PKM2 interacts with hypoxia-inducible factor 1α (HIF1α) and activates the HIF-1α-dependent transcription of enzymes necessary for aerobic glycolysis in macrophages. Knockdown of PKM2, HIF1α and glycolysis-related genes uniformly decreases lactate production and HMGB1 release. Similarly, a potential PKM2 inhibitor, shikonin, reduces serum lactate and HMGB1 levels, and protects mice from lethal endotoxemia and sepsis. Collectively, these findings shed light on a novel mechanism for metabolic control of inflammation by regulating HMGB1 release and highlight the importance of targeting aerobic glycolysis in the treatment of sepsis and other inflammatory diseases. The role of metabolic reprogramming in the regulation of innate inflammatory response remains incompletely understood. Here, the authors show that pyruvate kinase M2-mediated aerobic glycolysis contributes to inflammatory response, and that inhibition of this pathway protects mice from lethal endotoxemia and sepsis.